Compensation in International Licensing Agreements - Aulakh, Preet S.; Cavusgil, S. Tamer; Sarkar, MB. (Journal of International Business Studies, 1998)
This study examines licensing agreements between independent firms based on their compensation structures. We first suggest that a licensor's ability to monitor and influence foreign licensees is related to the type of compensation used in structuring the relationship. Next, we identify a set of factors, related to host country conditions where the technology is licensed, stage in the technology life cycle, and licensor firm characteristics, that impact the choice between different compensation structures. Empirical findings based on a survey of U.S. firms generally support the hypotheses proposed in this study.